A Leadership Journey: Personal Reflections from the School of Hard Knocks - R. Scott Pochron (Integral Review, 2009)
The following paper chronicles the evolution of the author’s thinking onleadership through the course of his work experience. Leadership is viewed as adynamical process involving both formal and informal roles. The process is initiated asan individual identifies opportunities and feels pulled to respond to emerging patterns andinitiate action to enable positive change. The dynamics between formal and informalleadership structures and leadership as a state of mind are discussed.